Wildlife in Disturbed Forests: Reptile and Amphibian Diversity in South Papua - Maulida, Risqinanti; Chelvin Cahya Kirnanda; Mirza Dikari Kusrini; Ani Mardiastuti (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
The unavoidable economic development in Papua will certainly cause habitat changes. The logging activities in the production forest areas provide various habitat types with different typologies based on the clearing of areas for timber production and human access in each habitat. This research aims to analyze the diversity, richness, evenness, and similarity of reptile and amphibian communities in relation to the type of habitat disturbance in the Production Forest Area of Boven Digoel, Papua. Field surveys were conducted in June-July 2023, using active and passive survey methods in highly disturbed, moderately disturbed, and undisturbed habitats. The Shannon diversity index values of herpetological diversity in the three habitat types ranged from 0.75 to 1.94. Highly disturbed habitats have the lowest number of individuals and species of reptiles and amphibians. However, the common reptiles and amphibians are found in undisturbed habitats. Two species of protected reptiles were recorded in this area. This indicates that some species are at risk of extinction if action is not taken to conserve their habitats.